Factors Related To Compliance With Pregnant Women Consuming Fe Tablet - Dewi Astuti; Anggraini Anggraini; Susilawati Susilawati; Nita Ervianasari (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
ABSTRACT: THE FACTORS CONCERNING ADHERENCE OF PREGNANT WOMEN TAKING FE TABLETS AT TULANG BAWANG I HEALTH CENTER IN 2021 Background : Anemia in pregnancy is a national problem because it reflects the value of the community socio-economic welfare, and has a significant influence on the quality of human resources. Based on the Baseline Health Research (Riskesdas) report (2018), the proportion of anemia has increased by 11.8% compared to 2013 report. The results of Baseline Health Research in 2018 show that in Indonesia the incidence of anemia in pregnant women was 48.9%. This number has increased in comparison with the Baseline Health Research data in 2013 amounted to 37.1% and 14.0% in 2007. Objectife : The purpose of the study was to determine the factors concerning adherence of pregnant women taking Fe tablets at Tulang Bawang 1 Health Center in 2021.Methods : This study method was quantitative using an analytical survey. The population in this study were pregnant women in their second and third trimester registered at the TulangBawang I Health Center who experienced anemia amounting to 54 respondents as of July 16, 2021. The sampling technique used in this study was the Accidental Sampling. The sample size in this study was 54 respondents.Results and Conclusion : The results showed that there was a significant relationship among knowledge (p value: 0.01, OR 1.72), education background (p value: 0.008), and attitude (p value 0.77) with the adherence of pregnant women to take Fe tablets at the TulangBawang I Health Center in 2021. There was no relationship between family support (P value: 0 ,59) with the adherence of pregnant women to take Fe tablets at the TulangBawang I Health Center in 2021. Suggestions for respondents are that pregnant women are expected to add more insight to seek information from both health workers and the mass media and routinely attend classes for pregnant women so that they understand more about the importance of taking tablets Fe.Keywords: Knowledge, education, attitude, family support, Adherenceof Taking FE tablet pregnant women ABSTRAKLatar Belakang : Anemia pada kehamilan merupakan masalah nasional karena mencerminkan nilai kesejahteraan sosial ekonomi masyarakat, dan pengaruhnya sangat besar terhadap kualitas sumber daya manusia. Berdasarkan laporan Riskesdas (2018), proporsi anemia mengalami peningkatan sebanyak 11,8% dari tahun 2013. Hasil Riskesdas tahun 2018 menunjukan bahwa di Indonesia kejadian anemia pada ibu hamil sebesar 48,9% ibu. Hal ini mengalami peningkatan jumlah dimana pada data Riskesdas tahun 2013 hanya berjumlah 37,1 % dan 14,0% pada tahun 2007.Tujuan : Tujuan penelitian ini diketahui Faktor-Faktor yang Berhubungan dengan Kepatuhan Ibu hamil mengkonsumsi Tablet Fe di Puskesmas Tulang Bawang 1 Tahun 2021.Metode : Penelitian ini menggunakan metode kuantitatif dengan menggunakan survey analitik. Populasi dalam penelitian ini adalah Ibu hamil TM II dan TM III di Puskesmas Tulang Bawang I yang mengalami anemia berjumlah 54 responden per tanggal 16 Juli 2021. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah dengan menggunakan teknik Accidental Sampling. Besarnya sampel dalam penelitian ini 54 responden.Hasil dan Kesimpulan : Hasil penelitian didapatkan ada hubungan yang signifikan antara pengetahuan (p value: 0,01, OR 1,72), pendidikan (p value : 0,008), sikap ( p value 0,77) dan tidak ada hubungan dukungan keluarga ( P value : 0,59) dengan kepatuhan ibu hamil mengkonsumsi tablet Fe di Puskesmas Tulang Bawang I Tahun 2021. Saran bagi responden diharapkan ibu menambah wawasan lebih banyak mencari informasi baik dari tenaga kesehatan maupun media massa dan rutin mengikuti kelas ibu hamil agar ibu lebih memahami tentang pentingnya mengkonsumsi tablet Fe. Kata Kunci : Pengetahuan, pendidikan, sikap, dukungan keluarga, kepatuhan konsumsi tablet FE ibu hamil